Sugar transporters enable a leaf beetle to accumulate plant defense compounds - Zhi-Ling Yang (Nature Portfolio, 2021)
The herbivorous horseradish flea beetle sequesters plant toxins to defend against predators. Here the authors identify glucosinolate transporters expressed in the beetle Malpighian tubules and provide evidence that these reabsorb glucosinolates from the tubule lumen to prevent their loss by excretion.